A multi-phase, multi-component model for coupled processes in anaerobic landfills: theory, implementation and validation. Issue 9 (28th September 2021) - Lu, Shi-Feng; Feng, Shi-Jin; Zheng, Qi-Teng; Bai, Zhen-Bai
Abstract : To describe the long-term coupled behaviour of landfilled municipal solid waste (MSW), this paper proposes a numerical model based on the theories of the conservation of mass, momentum and energy of porous media over a three-phase solid–liquid–gas system. Compared with currently available coupled models, the proposed model can simultaneously simulate such physical processes as phase change, dissolution of the gas phase, the diffusion of its components, evaporation in the liquid phase and changes in the pH of leachate, as well as its solute migration. The finite-volume method was used to numerically discretise the governing equations, with a sequentially iterative technique used for the numerical model of the solution. The corresponding computer code was formulated on the open-source platform OpenFoam. The model was then used to simulate the famous MSW degradation consolidating anaerobic reactor experiment conducted at Southampton University, where the results generally agreed well with the experimental data. The proposed model was also applied to capture spatial and temporal variations in the skeleton of MSW, leachate and landfill gas in a simplified two-dimensional landfill. Overall, the work here provides a basic coupled framework for simulating the long-term behaviours of landfilled MSW. It can be improved upon in future research by implementing other, more reasonable, constitutive relations of MSW.